Influence Of Islamic Civilization History On Secondary School Students’ Understanding Of Cultural Diversity In National Value Classes In Zamfara State, Nigeria - Sule Muhammad; Sabiu Lawal (MAQOLAT: Journal of Islamic Studies, 2026)
This study examined the influence of Islamic Civilization History on secondary school students’ understanding of cultural diversity in National Values Classes in Zamfara State, Nigeria. With Nigeria’s diverse ethnic and religious landscape, fostering tolerance and civic responsibility among students remains a key educational objective. Grounded in the Cultural Transmission Theory, the research explored how integrating Islamic historical and ethical teachings into classroom instruction can enhance students’ intercultural awareness and moral development. Employing a descriptive survey design, the study involved 370 Upper Basic III students selected through a multi-stage sampling technique from public and private schools across three Local Government Areas. Data were collected using a structured questionnaire and analyzed with descriptive statistics, Pearson correlation, and t-tests. Findings revealed that Islamic Civilization History is moderately to highly integrated into National Values Classes, significantly influencing students’ understanding of cultural diversity (???? = 0.421, p < 0.05). Exposure to Islamic historical content positively affected students’ attitudes toward cultural tolerance (t = 3.97, p < 0.05), and a strong correlation was observed between students’ knowledge of Islamic Civilization History and their appreciation of multicultural values (r = 0.486, p < 0.05). The study concludes that embedding Islamic historical narratives within National Values Classes fosters empathy, respect, and social inclusivity among students. Effective teaching strategies, adequate instructional resources, and teacher competence are critical in translating historical knowledge into positive attitudes. The findings underscore the importance of incorporating Islamic Civilization History into value education curricula to nurture culturally sensitive, morally grounded, and socially responsible individuals in Zamfara State and similar multicultural contexts.